Illustrated history of Indian enterprise (New Delhi, 2013)
An evocative account of Indian entrepreneurship and entrepreneurs from the dawn of civilization to the present, this volume updates FICCI's earlier publication Footprints of Indian Enterprise: Indian Business through the Ages (subsequently reproduced as A Pictorial History of Indian Business) to include contributions from some of the new names that have emerged in Indian business. Broadly classifying the Indian business story into pre- and post-Independence eras, this volume examines the policies and institutions that have enabled growth, studies the entrepreneurial role of the private sector and the role and position of PSUs in the current scenario, and looks at the possible future course for Indian business. With articles by Dwijendra Tripathi, T.C.A. Srinivasa-Raghavan, R. Champakalakshmi, and Shireen Moosvi, among others, and illustrated with more than 200 colour visuals, this volume offers a multidimensional study of Indian business from the Harappan civilization to the twenty-first century.
Keywords: "Economic history, Enterpreneurship, India"